Xenobiotics concentration and mobility in bovine milk from Italian farms - Beni, C.; Marconi, S.; Pennelli, B.; Ronconi, B. (Progress in Nutrition, 2007)
In sixty Italian dairy farms, with both conventional and biological bovine milk production, representative of the national situation, samples of different matrixes were analyzed in order to evaluate the presence of potential contaminant elements. In bovine milk chain (soils, irrigation and clear water, forages, integrators, unifeed and milk), quantitative analysis were performed with regard to heavy metals (Cd, Hg, Ni, Pb, Cu, Zn), metalloides (As, B) and non-metals (Se). The results obtained show that in some cases Cd, Pb and Zn concentrations in unifeed are over the legal limits; concerning milk, we have a decrease of boron and copper and an increase of selenium. As a conclusion the results obtained suggest that no toxic risk can be expected on milk production and consequently on human health. However, screening of matrix and contamination source are necessary to fix appropriate reference law limits for xenobiotics concentration in milk.